2012
DOI: 10.1038/aps.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ2 and PTPRD gene polymorphisms influence type 2 diabetes patients' response to pioglitazone in China

Abstract: Aim: To investigate the influence of peroxisome proliferator-activated receptor γ2 (PPAR-γ2) gene polymorphism rs1801282 and protein tyrosine phosphatase receptor type D (PTPRD) gene polymorphism rs17584499 on the occurrence of type 2 diabetes and pioglitazone efficacy in a Chinese Han population. Methods: One hundred ninety seven type 2 diabetes patients and 212 healthy controls were enrolled. Among them, 67 type 2 diabetes patients were administered pioglitazone (30 mg/d, po) for 3 months. All the subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 38 publications
3
33
0
2
Order By: Relevance
“…This study also indicated that P12A mutation might also be linked to adipogenesis [66]. Furthermore, various research groups have shown that biological variability linked with the glucose-lowering effect of pioglitazone is also partly ascribed to the polymorphism associated with PPARG gene [6769]. The PTPRD SNP rs17584499, located in intron 10, has been identified in Chinese populations as another important factor leading to pharmacodynamic variability in the glucose-lowering effect of pioglitazone [69].…”
Section: Pharmacogenomics and Pharmacogenetics Of Pioglitazone In Diabetesmentioning
confidence: 97%
See 1 more Smart Citation
“…This study also indicated that P12A mutation might also be linked to adipogenesis [66]. Furthermore, various research groups have shown that biological variability linked with the glucose-lowering effect of pioglitazone is also partly ascribed to the polymorphism associated with PPARG gene [6769]. The PTPRD SNP rs17584499, located in intron 10, has been identified in Chinese populations as another important factor leading to pharmacodynamic variability in the glucose-lowering effect of pioglitazone [69].…”
Section: Pharmacogenomics and Pharmacogenetics Of Pioglitazone In Diabetesmentioning
confidence: 97%
“…Furthermore, various research groups have shown that biological variability linked with the glucose-lowering effect of pioglitazone is also partly ascribed to the polymorphism associated with PPARG gene [6769]. The PTPRD SNP rs17584499, located in intron 10, has been identified in Chinese populations as another important factor leading to pharmacodynamic variability in the glucose-lowering effect of pioglitazone [69]. A substantial alteration of pioglitazone-induced reduction in HbAlc was observed in ADIPOQ C-11377G genotype and ADIPOR2 G795A genotype in Chinese and Iranian T2D populations [43,70].…”
Section: Pharmacogenomics and Pharmacogenetics Of Pioglitazone In Diabetesmentioning
confidence: 99%
“…In 197 Chinese Han T2DM patients of whom 67 patients were given pioglitazone (30 mg/day for 12 weeks), those patients with PPARγ2 gene polymorphism rs1801282 CG showed significantly higher levels of PPPG and serum triglyceride compared with those with rs1801282 CC genotype 28. In patients with protein tyrosine phosphatase receptor type D gene polymorphism rs17584499, the CC genotype had better PPPG levels compared with CT + TT genotypes 28.…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…In patients with protein tyrosine phosphatase receptor type D gene polymorphism rs17584499, the CC genotype had better PPPG levels compared with CT + TT genotypes 28. In 241 Chinese patients with T2DM of whom 41 patients were given rosiglitazone (4 mg daily for 12 weeks), the presence of the SNPs Thr394Thr and Gly482Ser of the PPARγ coactivator-1 gene increased the therapeutic efficacy of rosiglitazone when compared to controls 29…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…Interestingly, in this study rs17584499 was found to be associated also with pioglitazone therapeutic efficacy. In fact, patients with rs17584499 CT+TT genotypes showed significantly lower differential value of postprandial plasma glucose compared to those with CC genotype after pioglitazone treatment for 3 months [58]. …”
Section: Ptprf and R2a Ptp Subfamilymentioning
confidence: 99%